Identity and Cultural Dimension of the Inner Spaces in the Kurdish Dwelling - Akram Faraedon Hamaamen; Hawre Sarkawt Rashed (Zanco Journal of Humanity Sciences)
The current research aims to identify the "identity and cultural dimension of the inner spaces of the Kurdish dwelling", from The concept of culture has evolved as a result of the great development in all cities of the world, and since culture is linked to the components of society, it plays different roles in the formation of cultural awareness of the members of society regardless of its level of development, and for the cultural components of the Kurdish society, it includes the language and religion that constitute. This study aims to highlight the main focus of achieving the cultural and social identity of Kurdish dwellings in the city of Soleimania, which reflects the impact of the cultural heritage of Kurdish society.